Infant learning platform using Arduino (project 2) - Yiak, Rachel Si Tong (2019)
Early childhood learning can be stimulated with the use of sound and visual cues. Many existing studies explored the experience and benefits of using such interactivity when building a toy. The objective of this final year project is to understand the basics of childhood learning, and to design and build a prototype that fits the brief of having a focus on problem solving. Using the Arduino platform, the toy can take in simple inputs from the child. The research is explored deeper by upgrading into a modifiable toy via a mobile application. The report begins with an overview of interactive toys and customisability. Early childhood learning and previous studies will be discussed under the literature review. The following chapters will elaborate on the methodology and implementation of the toy. The report will then conclude with a section on reflection and future work.